Direct Aryloxylation/Alkyloxylation of Dialkyl Phosphonates for the Synthesis of Mixed Phosphonates. (3rd May 2018) - Huang, Hai; Denne, Johanna; Yang, Chou‐Hsun; Wang, Haobin; Kang, Jun Yong
Abstract: A strategy for the direct functionalization strategy of inertial dialkyl phosphonates with hydroxy compounds to afford diverse mixed phosphonates with good yields and functional‐group tolerance has been developed. Mechanistic investigations involving both NMR studies and DFT studies suggest that an unprecedented highly reactive P V species (phosphoryl pyridin‐1‐ium salt), a key intermediate for this new synthetic transformation, is generated in situ from dialkyl phosphonate in the presence of Tf2 O/pyridine. Abstract : Mild und metallfrei : Tf2 O wurde genutzt, um elektrophile Phosphorspezies zu erzeugen. Eine derartige metallfreie Aktivierung beständiger Dialkylphosphonate ermöglicht die Synthese diverser gemischter Phosphonate unter milden Bedingungen für zahlreiche Substrate mit hervorragender Toleranz für funktionelle Gruppen. NMR‐ und DFT‐Studien geben Einblick in den Mechanismus.